Orthodontic Debonding Procedures: A Survey of Thai Orthodontists - Anurukkulkij, Buranee; Sirabanchongkran, Supassara (Thai Journal of Orthodontics, 2025)
Background: Orthodontic debonding procedures impact enamel integrity. Despite various proposed techniques, no standardized protocol exists. Understanding commonly used methods among Thai orthodontists may aid in developing practical, evidence-based guidelines. Objective: To investigate current practices of Thai orthodontists regarding bracket removal, adhesive removal, and enamel polishing during debonding, aiming to identify prevailing clinical trends and support standardized protocol development. Materials and methods: A structured four-part questionnaire was distributed to 726 active members of the Thai Association of Orthodontists via electronic message and postal mail. It covered: 1) respondents’ general background; 2) bracket type, surface preparation, and adhesive system frequently used; 3) debonding instruments and procedures for metal and ceramic bracket debonding; and 4) adhesive removal, enamel polishing, and time spent. Descriptive statistical analyses were performed. Results: 389 orthodontists (53.58 %) responded; and 388 responses were analyzed. Bracket debonding pliers were most frequently used, typically applying squeezing force occlusogingivally. For adhesive removal, up to four instruments were used sequentially, with high-speed white stone bur favored in both one- and multi-step methods. Rubber cup with slurry pumice was common for enamel polishing. Water was the primary coolant used in both adhesive removal and enamel polishing. Most entire procedures took under 15 minutes per arch. Conclusion: Variability in orthodontic debonding practices among Thai orthodontists was observed, the findings suggest that instrument selection is influenced by the need to balance clinical effectiveness with procedural efficiency, aiming to achieve optimal outcomes within a reasonable chair time.